The Role of ‘Conservation’ and ‘Dynamism’ in the Revitalisation of Architectural Heritage based on the Continuity of Place-bound Values The Case of Choghaznabil Historic Site - Shima Shahrokhi; Kamaledin Niknami; Mohammad Saeed Izadi (صفه)
The revitalisation approach in the field of architectural heritage conservation requires the identification and enumeration of all related values. However, little attention has been paid in processes of revitalisation to natural geography and human thought, namely, place values. Shortcomings in recognising and explaining these values lead to a loss of an influential natural environment and the integration of architectural heritage with its context. On the other hand, in order to protect the architectural heritage, it is essential to recognise the continuity of values over time on top of identifying all relevant values. This study aims to improve the knowledge of valuation and develop a value-oriented view in architectural heritage protection, as well as developing current classifications of values and introduce the concept of ‘continuity’. Adopting a qualitative approach and logical reasoning strategy, this study investigates the concepts of ‘place values’ and ‘continuity’ in architectural heritage, by re-reading related texts and theories, and then by analysing the data, the components of ‘continuity’, ‘Place value indices’, and their enumeration dimensions have been extracted as research findings and used to formulate the conceptual framework of ‘architect ural heritage revitalisation based on the continuity of place values’. Finally, by analysing the theoretical and field data obtained from the study of Choghaznabil Complex, the main question of the research is to do with the approach to revitalise the architectural heritage to perpetuate place values. Findings show that the relationship between the three indicators of ‘natural foundations’, ‘construction idea’ and ‘constructed edifice’ forms place values that can be identified in the four dimensions of landscape, structure, function and meaning in architectural heritage. Also, ‘dynamics’ and ‘conservation’ are found as the two components of continuity, and the continuation of place values is subject to the ‘dynamics’ of indicators applied to ‘sustainable development’ and ‘conservation’ approaches in the relationship between indicators with the approach of ‘disaster risk reduction’ in the revitalisation process.